MICROSCOPIC FACTORS AFFECTING PORE GEOMETRY AND PORE STRUCTURE AND THE DEVELOPMENT OF A ROCK TYPE CURVE FOR ROCK TYPING SANDSTONES RESERVOIR - TRIVIANTY MUSU (NIM : 32212008), JUNITA
Previous studies in general indicate that reservoir characterization including rock typing should be done by integrating geological information with related engineering aspects. Indeed, several earlier researchers claimed that a formation or rock deposited in similar conditions and through similar diagenetic processes has a certain rock type that produces a group of capillary pressure curves with certain curve shape characteristics. Unfortunately, this statement has not been examined further comprehensively by not only relying on capillary pressure data. Until now there has been no method of rock typing for sandstones that is universally applicable and consistent in the context of the relations among physical properties of the rocks and with the microscopic geological characters. Material sources, depositional environments, and diagenetic processes can vary greatly. Therefore, sandstones are quite complex in terms of rock forming components, textures, and their diagenesis results. Hence, this study aims to characterize the sandstone reservoir based on its microscopic geological factors including mineralogy composition and its mode of occurrences, texture and diagenesis that affect pore geometry and pore structure in an effort to develop a method of sandstone rock typing which can be universally applied and consistent. The approach used in this research is an investigation of a qualitative relation between capillary pressure curve characters in the form of J-Function and microscopic features of the rocks, and a mathematical application of similarity concept. The concept of similarity is actually a concept that manifests the behavior of natural objects in the form of a power law equation. The Kozeny-Carman equation that links among physical properties of rocks is used to form a power law equation that relates pore geometry in the form of a dependent variable (k/)0,5 to pore structure in the form of an independent variable (k/3). For sandstones, the similarity of pore structure can be confirmed to be closely related to similarity in microscopic geological characters. The study used 1342 data sets of sandstone core plugs, consisting of routine core (RCA), thin section petrography, scanning electron microscope (SEM), x-ray diffraction (XRD), and special core analysis (SCAL). These data come from oil and gas fields located in 8 (eight) sedimentary basins throughout Indonesia with various number of formations. One data set from a sandstone reservoir was separated as a blind data set for the purpose of validating the main research results. The results showed that sandstone samples having capillary pressure data transformed to a J-Function curve have similar geological characteristics, rock forming minerals, textures, and diagenesis events. Since J-Function mathematically expresses the pore structure in terms of tortuosity, the sandstone samples all thus have a similar pore structure. The Kozeny-Carman equation in the form of a power law relating the pore geometry variable (k/)0,5 to the pore structure variable (k/3) indicates that sandstone samples with a similar pore structure can have a certain power law equation. This equation becomes a rock type equation for which a rock type is characterized by a value of the power law exponent formed based on resulted from plotting (k/)0,5 versus (k/3) on a log-log graph. Overall, the results show that rock type equations obtained have high correlation coefficients, ranging from 0.73 to 0.99, with power law exponents b between 0.208 and 0.441. The physical meaning of exponent b may represent the quality of rock type. The lower the value of b, the poorer the quality of the rock type. Grouping close values of b between neighboring rock types and averaging b for each group lead to the construction of a type curve or family curve for the sandstones. Validating the type curve is performed by using the blind data, resulting in excellent agreement with those obtained from rock grouping by using combined J-Function and the corresponding microscopic geology data. Conclusions and the novelty 1) this research is the first comprehensive one on sandstone samples by employing 1342 core plugs obtained from eight different basins, 2) a single J-Function should be a representation for samples having similarity in microscopic geological characters, 3) a method of rock typing based on a power law of Kozeny-Carman equation has been successfully constructed in a form of type curve (family curve) for sandstones. Application of the method is consistent with J-Function grouping. Results of the present research offer 1) a better understanding of the relationship between geological and engineering aspects in the context of sandstone rock typing, 2) a method of rock typing that only needs routine core analysis data and is easy and fast to use, and 3) a conformity in using both the method and J-Function for the purpose of modeling sandstone reservoirs.